Evaluating the Effectiveness of an Instructional Intervention in Knowledge Acquisition about Diet Therapy among Patients with Spinal Cord Injuries - Shalash, Ali A.; Mousa, Ayad M. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Patients with spinal cord injuries often face unique challenges related to their dietary regimen. Adequate knowledge about dietary regimens is crucial for their overall health, well-being, and management of specific nutritional needs. Objectives: To evaluate the effectiveness of the instructional intervention in enhancing knowledge about dietary regimens among patients with spinal cord injuries and to compare the knowledge levels between the intervention group and the control group. Patients and Methods: The study was conducted from 8th of March 2023 to 15th of February 2024. Sixty patients at Ibn Al-Kuff Hospital for Spinal Cord Injuries in Baghdad were studied based on power analysis to detect the difference in knowledge acquisition between the intervention and control groups. The targeted age was 18-60 years. Individuals with cognitive impairments affecting comprehension were excluded. Participants were randomly assigned to either the intervention or the control group using computer-generated randomization. A structured instructional program was administered to the intervention group to enhance knowledge about diet therapy, while the control group received no specific intervention. Pre- and post-intervention assessments were conducted to evaluate participants’ knowledge levels. The assessments employed a validated rating and scoring scale tailored for assessing knowledge about dietary regimens in the context of spinal cord injuries. Results: In pre-intervention, both groups had poor knowledge scores but in post-intervention, the intervention groups mean became good while the control group’s score remained “moderate”. the intervention group showed a notable increase in knowledge (p < 0.05), while the control group had a non-significant improvement (p = 0.345). Conclusion: The dietary intervention had a positive impact on enhancing participants’ knowledge levels related to dietary therapy for spinal cord injuries. Continued assessment and multidisciplinary strategies should be prioritized to ensure the provision of effective and holistic support services to patients with spinal cord injury.